Innovation of simple binoculars as a teaching aid for optical practicum at school. Issue 1 (1st January 2022) - Azhar; Fuadi, H; Doyan, A; Susilawati; Ayub, S; Hudha, L S
Abstract: Learning aids are tools used by teachers in learning and prevent verbalization in students. The purpose of this research is to make simple earth telescopes as visual aids for optical practicum in schools. The method used is the experimental method, namely analyzing, designing, making and testing the props made. The subjects of the research were 17 students of physics education FKIP University of Mataram. The binoculars test saw the object of letters and writing with the font Times New Roman 350 at a distance of 50 meters and 100 meters. The results showed that the object was clearly visible with the satisfaction level of using the teaching aids a score of 3.71 the criteria were satisfied and suitable for use. The use of simple earth telescopes is suitable for use in optical practicums in schools. Teachers are expected to be able to create and develop teaching aids to improve students' understanding of concepts.